Pemanfaatan Game Edukasi PENTING (Peduli Stunting) Flashcards sebagai Media Pembelajaran MP-ASI pada Ibu Balita di Puskesmas Purwokerto Utara II - Kania Sayidatina Putri; Ade Tuti Turistiati; Prita Suci Nurcndrani (Jurnal Nomosleca, 2025)
The purpose of this study was to determine the effect of using the PENTING (Care for Stunting) Flashcard game at Purwokerto Utara II Health Center as a medium for educational campaigns on complementary feeding (MP-ASI) for mothers of toddlers at the same health center. This study involved 35 mothers of toddlers who were selected purposively. This study used a pre-experimental design with a One-Group Pretest-Posttest Design model. There were two treatment conditions: one using flashcard media and one without flashcard media. The research tool consisted of twenty-five multiple-choice questions. Based on the results of the paired t-test, H0 was rejected and H1 was accepted, which showed a calculated t-value of 9.514, which was higher than the t-table value of 2.441. In other words, there was a difference between the average pretest and posttest results, which indicated that flashcard media increased mothers' understanding of complementary feeding (MP-PASI).